Проблеми використання дронів у задачах обприскування сільськогосподарських культур та шляхи їх вирішення. - Діордієв, Володимир Трифонович; Кашкарьов, Антон Олександрович; Семендяєв, О.Є. (Мелітополь, ТДАТУ, 2019)
UKR: У статті піде мова про проблеми використання дронів для обприскування сільськогосподарських культур, а саме садів і виноградників. Детальна обґрунтована актуальність напряму та галузь використання. Для цього використані статистичні дані галузі в Україні. На основі огляду наукових та науково-популярних видань за питанням використання сучасних цивільних безпілотних літальних апаратів, були визначені сильні та слабкі сторони, а також можливості і загрози їх використання за проблематикою статті. З метою подолання вказаних проблем використання дронів у задачах обприскування, запропонована концепція напівавтономного дрону з обмеженим функціоналом. Розглянуті основні функціональні елементи сучасних дронів. Акцентована увага на використанні асинхронних двигунів з короткозамкненим ротором для приводу.

|ENG: The article deals with the problems of using drones for spraying crops, namely orchards and vineyards. The relevance of the direction and scope in this area are justified. Industry statistic data of Ukraine are used. Based on a review of scientific and popular science publications on the use of modern civil unmanned aerial vehicles, strengths and weaknesses were identified, as well as the opportunities and threats of their use. In order to overcome these problems with the use of drones, the concept of a semi-autonomous drone with limited functionality is proposed. As a result of the analysis of information sources, in the conditions of gardening, it is advisable to carry out the synthesis of a boom sprayer, elements of small aviation and UAVs. This direction will increase the efficiency of processing gardens by reducing processing costs (increasing the speed of work, lowering the requirements for dispersion of the working solution, increasing the reliability of the equipment) and improving the quality of processing (increasing the depth of aerosol penetration, reducing the removal of working solution by the wind). Attention is focused on the use of squirrel-cage induction motors for driving propellers from a high-frequency power source. The results of the work will increase the useful weight of the drone, increase the operating time and efficiency of use in horticulture and viticulture. The above becomes possible by increasing the width of the grip, increasing the processing speed and the depth of penetration of working solutions into the crown of a tree or bush. This will reduce the cost of fuels and lubricants, increase the quality and speed of processing, reduce the requirements for weather conditions for work. Tasks for further work: - justification of the design and selection of electric power equipment (frame, hydraulic fittings, motors, switchgears, sensors, formalization of the control system); - determination of the main parameters on which the process of using the working solution in processing the culture and the influence of environmental factors will depend; - study of the operation of an induction motor when powered by a high frequency network in continuous mode; - definition and correlation of economic and qualitative components of the practical use of the complex. The final results can be used when spraying orchards, vineyards, corn, sunflowers and other crops, as well as form the basis of other industry solutions. повітряних гвинтів. Поставлені завдання для подальшої роботи.
PROBLEMS OF DRONE USE IN SPRAYING AGRICULTURAL CROPS AND WAYS OF THEIR SOLUTION
Keywords: spraying; unmanned aerial vehicle; drone; agriculture; gardening; обприскування; безпілотний літальний апарат; дрон; сільське господарство; садівництво